Trials by media, some cases - Iker Nabaskues (Oñati Socio-Legal Series)
This article deals with different trial-by-media cases. First of all, some paradigmatic cases are cited that occurred in the United States where the media played an important role in spreading ideas to the population that later had consequences on judicial proceedings. Secondly, a Spanish example is given where a person found guilty of murder was later exonerated. The Spanish case, the media, although many years later, represents an interesting form of civil reparation. The Rocío Wanninkhof case is one of the most important cases of miscarriage of justice in the history of the country. In this case, the alleged perpetrator of the crime, Dolores Vázquez, was imprisoned. This is a very interesting case for the Law & Media field of analysis. The role played by the media in the resolution of the case can be considered as a paradigm of violation of the principle of the presumption of innocence of citizens. Likewise, the role of the media years later, producing a documentary on the case, can be considered a sort of a civil restitution of the alleged guilty and convicted. This element of restitution can also be considered as a socio-legal element to be taken into account in the future for similar cases.